Kesalahan Struktur Frasa Subordinatif Bahasa Mandarin - Aprilia Ruby Wikarti (Bina Nusantara University, 2015)
This research aimed to determine the misuse of subordinate phrase on the Chinese language learners. The samples of this study were texts written by fifteen 3rd grade students of Chinese Literature, Faculty of Humanities, University of Indonesia. This research applied qualitative approach with the method of error analysis. Result shows that five types of errors are found out; they are addition, omission, misordering, misselection, and blends. Omission is the most frequent error that comes up. Lack of understanding about subordinate phrase of the Chinese language is the most common reason of the error. To decrease the errors, students must improve their knowledge and competence about subordinate phrase of the Chinese language. They must increase the exercises and applications of the phrase as well.